REPRESENTASI SIKAP SOSIAL MASYARAKAT DAYAK BAKUMPAI DALAM FABEL DAYAK BAKUMPAI - Sri Wahyu Nengsih (Balai Bahasa Provinsi Papua, 2019)
Fable of Dayak Bakumpai is one of various fable spread out in Indonesia. This fabelindirectly represents noble cultural values of Bakumpai society. An understanding of sociallife, wisdom, and public policies of Dayak Bakumpai can be learned through the characterand nature of the animals in the fable of Dayak Bakumpai. This fable is ought to bepreserved, in order to sustainable. This writing briefly describes the representation of the sociallife of Bakumpai society in the fable Dayak Bakumpai. The method used in this writing isqualitative descriptive method with note taking technique, interview, and literature. The resultof the analysis provides a brief overview about social life representation of Dayak Bakumpaisociety in the fable Dayak Bakumpai.